A Real-World Data Study on the Healthcare Resource Use for Uncontrolled Moderate-to-Severe Atopic Dermatitis in Secondary Care in the United Kingdom Prior to the Introduction of Biologic Treatment - Hudson RDA; Ameen M; George SMC; Harwood CA; Weller RB; Lear JT; Rout R; Surendranathan T; Petrovic M; Bewley AP (Dove Medical Press, 2022)
Richard DA Hudson,1 Mahreen Ameen,2 Susannah MC George,3 Catherine A Harwood,4,5 Richard B Weller,6,7 John T Lear,8,9 Rajesh Rout,1 Thishi Surendranathan,1 Milos Petrovic,1 Anthony P Bewley4 1Sanofi, Berkshire, UK; 2Royal Free NHS Foundation Trust, London, UK; 3University Hospitals Sussex NHS Foundation Trust, Brighton, UK; 4Barts Health NHS Trust, London, UK; 5QMUL, London, UK; 6NHS Lothian, Edinburgh, UK; 7University of Edinburgh, Edinburgh, UK; 8Salford Royal NHS Foundation Trust, Salford, UK; 9Manchester Academic Health Science Centre, Manchester University, Manchester, UKCorrespondence: Richard DA Hudson, Sanofi, 410 Thames Valley Park Drive, Reading, Berkshire, RG6 1PT, UK, Email richard.hudson@sanofi.comBackground: Whilst there is international evidence around the high healthcare resource utilization (HRU) associated with atopic dermatitis (AD), there is a lack of published data from the United Kingdom (UK).Methods: A retrospective, descriptive, observational study was conducted to evaluate the burden of moderate-to-severe AD on the National Health Service (NHS) in an adult UK population treated with traditional standard of care prior to the introduction of biologics. Patients (n=59) were recruited from 6 UK NHS Hospital Trusts and observed over three years.Results: 707 dermatology clinic visits were recorded over the observation period, amounting to 6.6 visits per patient-year, most commonly for routine check-ups most of which involved dermatology consultants (n=469, 66%). Physicians were the most consulted healthcare professional (n=652, 92%); emollients were the most common treatment (n=80 courses). 174 flares requiring additional medical advice were recorded in total (1.6 per patient-year).Discussion/Conclusions: Complex treatment pathways for adult patients in the UK with moderate-to-severe AD incur considerable HRU, particularly for those patients non-responsive to systemic therapies with broad immunosuppressant action. Recent advances in biologics-based AD management could possibly have a significant positive impact on HRU through significant reduction in the number of NHS touch points identified in this study.Keywords: atopic dermatitis, healthcare resource use, observational study